Application of Project-Base Learning in Entrepreneurship Education in Indonesia - Pajala, Semuel; Rauf, Rusdiaman; Randy, Muh. Fuad (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
In the process of teaching entrepreneurship education, appropriate pedagogy is needed in realizing a curriculum that is contextual and relevant to the development of information technology and the need for the job market. This research aims to provide a comprehensive overview of entrepreneurship education with effective teaching methods by synthesizing existing research findings. This research method uses a systematic literature review approach to synthesize various academic database literature sourced from Scopus or Web of Science with keywords such as